DETERMINAN KEMISKINAN DAN KETIMPANGAN PENDAPATAN DALAM KONTEKS PEMBANGUNAN EKONOMI DAERAH: STUDI EMPIRIS - Andriani Karto; Sandi Hasudungan Pasaribu; Herman Paulus Fonataba (Politeknik Negeri Ambon, 2026)
Introduction: Poverty and income inequality remain fundamental challenges in Indonesia's regional economic development, where despite declining absolute poverty rates during decentralization, consumption inequality has significantly increased, offsetting the positive impacts of consumption growth on poverty reduction. Income inequality demonstrates a positive and substantial impact on poverty prevalence, while unemployment, human development, fiscal transfers, and employment structure significantly influence these phenomena through complex transmission mechanisms.This study analyzes the determinants of poverty and income inequality in regional economic development contexts, examines the mediating role of income inequality in the relationship between macroeconomic determinants and poverty, and identifies heterogeneous determinant patterns across regions with different geographical and structural economic characteristics.Method: This quantitative explanatory research employs balanced panel data from 34 districts/cities during 2019-2023 (170 observations), utilizing Fixed Effect Model and Random Effect Model regression analysis with Generalized Method of Moments system estimation, mediation analysis using Baron and Kenny method, and heterogeneity analysis across urbanized, transitional, and rural regions.Results: Income inequality emerges as the strongest determinant of poverty (β = 18.45, p < 0.01), followed by the open unemployment rate, the Human Development Index, and economic growth. The informal employment structure constitutes the strongest predictor of income inequality (β = 0.0034, p < 0.01). Income inequality serves as a partial mediation, with a 32% mediation proportion for the employment structure pathway and 24% for the economic growth pathway. Substantial heterogeneity exists across regional typologies, where HDI becomes critical in urbanized areas while income redistribution proves more crucial in rural regions.Conclusion: Integrated development policies encompassing the structural transformation of informal employment, human resource investment strengthening, and the implementation of inclusive growth with differentiated approaches based on regional typologies are recommended to reduce poverty and inequality effectively. Keywords: Economic Growth, Human Development Index, Income Inequality, Poverty, Regional Development.